An Ultrafast N-Glycoproteome Analysis Method Using Thermoresponsive Magnetic Fluid-Immobilized Enzymes - Fan, Zhiya; Liu, Tong; Zheng, Fei; Qin, Weijie; Qian, Xiaohong (Frontiers in Chemistry, 2021)
N-glycosylation is one of the most common and important post-translational modifications, and plays a vital role in the control of many biological processes. The increasing discovery of abnormal alterations of N-linked glycans associated with many diseases leads to greater demands for rapid and efficient N-glycosylation profiling in large-scale clinical samples. In the workflow of global N-glycosylation analysis, enzymatic digestion is the main rate-limiting step, including both protease digestion and PNGase F deglycosylation. Prolonged incubation time is generally required due to the limited digestion efficiency in the conventional in-solution digestion method. Here, we propose novel thermoresponsive magnetic fluid (TMF)-immobilized enzymes (trypsin or PNGase F) for ultra-fast and highly efficient proteome digestion and deglycosylation. Unlike other magnetic material-immobilized enzymes, TMF-immobilized enzymes display a unique temperature-triggered magnetic response behavior. At room temperature, TMF-enzyme completely dissolves in aqueous solution and forms a homogeneous system with the protein/peptide sample for efficient digestion, but cannot be separated by magnetic force due its excellent water dispersity. Over its lower critical solution temperature (LCST), thermoflocculation of TMF-enzyme allows it to be easily recovered by temperature rising and magnetic force. Taking advantage of the unique homogeneous reaction of TMF-enzyme, both protein digestion and glycopeptide deglycosylation can be finished within three minutes and the whole sample processing time can be reduced for more than twenty times. The application of TMF-enzyme in the large-scale profiling of protein N-glycosylation in urine samples led to the successful identification of 2197 N-glycopeptides and further demonstrated the potential of this strategy for fast and high-throughput analysis of N-glycoproteome in clinical samples.